Species delimitation and microalgal cryptic diversity analysis of the genus Micractinium (Chlorophyta) - E. S. Krivina; A. D. Temraleeva; Yu. S. Bukin (Вавиловский журнал генетики и селекции)
In this article, the system of the green microalgal genus Micractinium, based on morphological, physiological, ecological and molecular data, is considered. The main diagnostic species characteristics and the taxonomic placement of some taxa are also discussed. Phylogenetic analysis showed that the genus Micractinium is characterized by high cryptic diversity. The algorithms used for species delimitation had different results on the number of potentially species-level clusters allocated. The ABGD method was less “sensitive”. The tree-based approaches GMYC and PTP showed a more feasible taxonomy of the genus Micractinium, being an effective additional tool for distinguishing species. The clustering obtained by the latter two methods is in good congruence with morphological (cell size and shape, ability to form colonies, production of bristles, chloroplast type), physiological (vitamin requirements, reaction to high and low temperatures), molecular (presence of introns, level of genetic differences, presence of CBCs or special features of the secondary structure in ITS1 and ITS2) and ecological characteristics (habitat). The polyphyly of the holotype of the genus M. pusillum as well as M. belenophorum is shown. The intron was effective as an additional tool for distinguishing species, and the results of the intron analysis should be taken into account together with other characteristics. The CBC approach, based on the search for compensatory base changes in conservative ITS2 regions, was successful only for distinguishing cryptic species from “true” members of M. pusillum. Therefore, to distinguish species, it is more effective to take into account all the CBC in ITS1 and ITS2 and analyze characteristic structural differences (molecular signatures) in the secondary structure of internal transcribed spacers. The genetic distances analysis of 18S–ITS1–5.8S–ITS2 nucleotide sequences showed that intraspecific differences in the genus ranged from 0 to 0.5 % and interspecific differences, from 0.6 to 4.7 %. Due to the polyphasic approach, it was possible to characterize 29 clusters and phylogenetic lines at the species level within the genus Micractinium and to make assumptions about the species.